380‐nm Ultraviolet Light‐Emitting Diodes with InGaN/AlGaN MQW Structure. Issue 4 (30th August 2013) - Bae, Sung‐Bum; Kim, Sung‐Bok; Kim, Dong‐Churl; Nam, Eun Soo; Lim, Sung‐Mook; Son, Jeong‐Hwan; Jo, Yi‐Sang
Abstract : In this paper, we demonstrate the capabilities of 380‐nm ultraviolet (UV) light‐emitting diodes (LEDs) using metal organic chemical vapor deposition. The epi‐structure of these LEDs consists of InGaN/AlGaN multiple quantum wells on a patterned sapphire substrate, and the devices are fabricated using a conventional LED process. The LEDs are packaged with a type of surface mount device with Al‐metal. A UV LED can emit light at 383.3 nm, and its maximum output power is 118.4 mW at 350 mA.